Utilization of banana (musa paradisiaca) peel as bioplastic for planting bag application - Huzaisham, Nur Athirah; Marsi, Noraini (IAEME Publication, 2020)
This research aims to utilise banana (Musa Paradisiaca) peel to be incorporated into biodegradable planting bag as well as to evaluate its mechanical and physical properties in order to compare with the commercial biodegradable planting bag. The preparation of samples involved several stages where banana peels (BP) were isolated from the chaff and chopped into smaller sizes about 2 cm in length. Then, the peels were oven-dried at 70℃ and grinded into the range diameter of 23 mm particle sizes. Dried ground banana peels were then extracted by maceration method and later were incorporated into thermoplastic starch (TPS) with eight different concentration of BP. Experimental tests were conducted to characterize and evaluate the mechanical and physical properties of the biodegradable plastic. In terms of density and porosity, bioplastic of 40 wt.% BP exhibited highest density and lowest porosity of 1.316 g/cm3 and 0.097% respectively. Furthermore, bioplastic of 10 wt.% BP withstand the highest tear resistance up to 66.388 N/mm. In terms of biodegradability, banana peel-based biodegradable plastic degraded much faster with average percentage of weight loss of 65.1% than that of the commercial biodegradable plastic with only average percentage of weight loss of 29.5% within the period of eight weeks.